2010
DOI: 10.1186/1471-2180-10-89
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic functioning and bradyrhizobial biodiversity of cowpea (Vigna unguiculataL. Walp.) in Africa

Abstract: BackgroundCowpea is the most important food grain legume in Sub-Saharan Africa. However, no study has so far assessed rhizobial biodiversity and/or nodule functioning in relation to strain IGS types at the continent level. In this study, 9 cowpea genotypes were planted in field experiments in Botswana, South Africa and Ghana with the aim of i) trapping indigenous cowpea root-nodule bacteria (cowpea "rhizobia") in the 3 countries for isolation, molecular characterisation using PCR-RFLP analysis, and sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 26 publications
10
79
1
Order By: Relevance
“…An exception is V. unguiculata (cowpea), where early studies showed that nine different cowpea genotypes collected from fields in different parts of Africa had diverse bradyrhizobial strains residing in nodules based on intergenic-spacer restriction length polymorphism analysis, and the nodules also accumulated different amounts of fixed N. However, greater Bradyrhizobium diversity was observed in plants growing in a South African soil compared with soils from Ghana and Botswana (Pule-Meulenberg et al 2010). A study of the nodule microbiomes of two different cowpea genotypes growing in Brazil reported that bacterial communities were influenced more by soil type than plant genotype (Leite et al 2017).…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…An exception is V. unguiculata (cowpea), where early studies showed that nine different cowpea genotypes collected from fields in different parts of Africa had diverse bradyrhizobial strains residing in nodules based on intergenic-spacer restriction length polymorphism analysis, and the nodules also accumulated different amounts of fixed N. However, greater Bradyrhizobium diversity was observed in plants growing in a South African soil compared with soils from Ghana and Botswana (Pule-Meulenberg et al 2010). A study of the nodule microbiomes of two different cowpea genotypes growing in Brazil reported that bacterial communities were influenced more by soil type than plant genotype (Leite et al 2017).…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…The ARC-IIC experimental station (Rustenburg) has clay percentage of 49.5 and receives an annual mean rainfall of 661 mm. Potchefstroom (ARC-GCI) has plinthic catena soil, eutrophic, red soil widespread (Pule-Meulenberg et al, 2010). The soil at Taung is described as Hutton, deep, fine sandy dominated red freely drained, eutrophic with parent material that originated from Aeolian deposits (Staff, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…While many studies in the past have focussed on plant species of economic importance, including soybean, common bean, cowpea, chickpea and red clover (Delorme et al, 2003;Laranjo et al, 2004;Kuklinsky-Sobral et al, 2005;Duodu et al, 2007;Hung et al, 2007;Laranjo et al, 2008;Ogutcu et al, 2008;Appunu et al, 2009;Chagas et al, 2010;Li et al, 2010;Pule-Meulenberg et al, 2010), native legume species have generally received less attention. In Belgium, legumes are restricted to the Faboideae subfamily and contain 102 plant species in 30 different genera (Lambinon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%